Comparative analysis of herbs ability Bajakah wood (Spatholobus littoralis), red betel (Piper crocatum), and Papuan red fruit (Pandanus conoideus) in preventing free radicals due to rhodamine-B injection - Noor Johan Andoyo Effendi; Juswono Unggul Pundjung; Latifah Risalatul; Palentek Gabriel Ada’; Faisal Muhammad (BIO Web of Conferences)
Rhodamine B is a carcinogenic additive that can trigger free radicals. Bajakah wood (Spatholobus littoralis), red betel (Piper crocatum), and Papua red fruit (Pandanus conoideus) are herbs with high antioxidants to ward off free radicals. This study analyzed the ability of the three herbs to fight free radicals due to rhodamine B injection. Eighty-five mice (Mus musculus) were divided into 17 treatment groups. The groups consisted of mice without herbs and rhodamine B, only with rhodamine B, and a combination of rhodamine B with certain herbal doses. Free radical measurements were carried out using Electron Spin Resonance (ESR), and cell damage was observed through histopathology. The effective doses were 7.27 mg/ml (Bajakah), 3.95 mg/ml (red betel), and 8.83 mg/ml (Papua red fruit). Free radicals decreased to 0.6 A.u (Bajakah), 0.8 A.u (red betel), and 0.7 A.u (Papua red fruit). Histopathology showed a decrease in cell damage by 44.7% (Bajakah), 30.2% (red betel), and 26.6% (Papua red fruit). The results of free radicals correlate with cell damage. Bajakah wood is the most effective herb for preventing free radicals.